2011
DOI: 10.3109/07435800.2011.566236
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Chronic Regular Exercise on Serum Ischemia-Modified Albumin Levels and Oxidative Stress in Type 2 Diabetes Mellitus

Abstract: Objectives. Our aim was to determine the effect of chronic regular exercise on ischemia-modified albumin (IMA) levels and oxidative stress in type 2 diabetes mellitus (DM). Design and methods. Sixty patients with type 2 DM were randomly divided into two groups as exercise (17 M, 13 F) and non-exercise (12 M, 18 F) groups, each consisting of 30 patients. The exercise group underwent a 3-month aerobic regular exercise consisting of moderate-intensity power walking. The non-exercise subjects remained sedentary th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
34
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(36 citation statements)
references
References 27 publications
1
34
0
1
Order By: Relevance
“…As shown in ESM Table 1, across 20 interventions of aerobic exercise training, [8,9,[22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38] the mean exercise frequency was three sessions per week, mean session duration was 48 min (not including warm-up and cool down), and mean exercise intensity was 74% of the HR max . In six trials (33%), exercise intensity was transformed from submaximal rates of V : O 2peak to the corresponding percentages of HR max .…”
Section: Resultsmentioning
confidence: 99%
“…As shown in ESM Table 1, across 20 interventions of aerobic exercise training, [8,9,[22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38] the mean exercise frequency was three sessions per week, mean session duration was 48 min (not including warm-up and cool down), and mean exercise intensity was 74% of the HR max . In six trials (33%), exercise intensity was transformed from submaximal rates of V : O 2peak to the corresponding percentages of HR max .…”
Section: Resultsmentioning
confidence: 99%
“…Most investigations involving IMA and physical activity have focused on the acute effects of exercise, [26][27][28][29] but only one study was found to investigate the chronic effects of exercise training (aerobic) in non-athletes 30 and no studies were found regarding RT and IMA levels. In this matter, three months of moderate-intensity walking unchanged IMA levels in type 2 diabetes mellitus patients, while its levels increased in the sedentary group.…”
Section: Discussionmentioning
confidence: 99%
“…Our study group consisted of outpatient individuals who attended regular check-ups. Reducing oxidative stress may be possible by various lifestyle modifications, such as changes in dietary intake (2), lowering insulin resistance and lipids via nutritional modifications (16), weight loss (14,16,26) and chronic exercise (27). However, the general consensus is that obesity is a cause of increased oxidative stress (14-17).…”
Section: Discussionmentioning
confidence: 99%